Improved mechanical and microstructural performance of high-density polyethylene–chitosan–hydroxyapatite composites as potential bone implant materials. (November 2022) - Shelly, M.; Raghavendra, M.; Prabhu, A.; Ravikumar, H.B.; Mathew, M.; Francis, T.
Abstract: High-density polyethylene (HDPE)–chitosan–hydroxyapatite hybrid composite series with varying concentration of hydroxyapatite were prepared and compared with its corresponding HDPE-chitosan binary composite. The microstructural and mechanical characterizations of the prepared composites were studied. A 12% increase for the composite system with 8 wt% hydroxyapatite (HA4) has been noted when compared with its corresponding binary system and has been optimized for further applications. The structural characterization and miscibility of the components in the composite system were studied by using Fourier transform infrared spectroscopy and X-ray diffractometry. Positron annihilation lifetime spectroscopy studies showed that the free holes are formed in the range of ∼115.8 Å 3 . Contact angle studies and sorption studies were further correlated with the biocompatibility analysis to study cell adhesion and protein absorption on the surface of the composites. MC3T3 E1 cell lines showed good cell proliferation on the optimized systems. The presence of micropores along with chitosan and hydroxyapatite promoted cell growth in the prepared composites. The current research study presents the development of an improved hybrid biocomposite material that has potential in biomedical implants. Graphical abstract: Image 1